The Relationship between Environmental Quality, Gross Domestic Product, Energy, Credit and Trade in Iran - ABBASIAN, Mojtaba; SHAHRAKI, Javad; AKBARI, Ahmad; HARATI, Javad (Journal of Environmental Management and Tourism, 2016)
Economic growth requires a greater use of energy and raw materials which in turn results in a higher level of environmental destruction and degradation of the environment. Almost all human economic activities, directly or indirectly affect the ecological system of the environment, extraction, production, transportation and consumption can all contribute to the degradation process of the environment increasing human activities on the ecological system in development in turn results in an expanding ecological imbalance This study tries to evaluate the effect of economic indicators GDP, consumption, trade and private sector credit quality of the environment in Iran from 1980 to 2014 using Bayesian causal map (BCM) in four scenarios. Examination of different impact levels for each of the four different stages. For a thorough analysis of carbon dioxide emissions led to a result indicating putting the blame on trade and commerce first and foremost, followed by private sector credit, energy consumption and finally the GDP. Furthermore, the results suggest that a drastic change in the four mentioned degrading factors may indeed result in less emission of carbon monoxide.
Keywords: BCM; GDP; Trade; CO2; Credit; Energy